(untitled) (Journal of Face Aesthetics, 2023)
The paper presents a thermographic image of the face of a 30-year-old patient before an autologous procedure using her own blood (CGF-Harmony) in the upper and middle parts of the face. The thermographic method is non-invasive, safe and non-contact. The possibility of using thermography in aesthetic medicine is important because it brings certain values, but one should be aware of the existence of certain limitations in thermography tests, resulting from many factors such as diet, use of various cosmetics, other environmental conditions and others.